Do idiosyncratic technology shocks induce peer effects? - Karpavičius, Sigitas; Yu, Fan (Journal of Corporate Finance, 2022)
Using a two-firm dynamic model, we investigate whether firms’ corporate policies are impacted by the peers’ idiosyncratic technology shocks. A firm hit by the positive idiosyncratic technology shock becomes more productive. Thus, it is better off. As a result, its Cournot competitor is worse off. Therefore, their optimal decisions are opposite to each other, leading to negative correlations between corporate policies across the firms. The empirical analysis using the idiosyncratic technology shocks and, to a lesser extent, CEO sudden deaths supports this prediction. Our analysis suggests that mimicking peers who alter their corporate policies due to idiosyncratic technology shocks destroys shareholder value.